1969
DOI: 10.1136/hrt.31.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of pulmonary blood flow after cavopulmonary anastomosis (Glenn operation).

Abstract: Anastomosis of the superior vena cava and right pulmonary artery (Glenn and Patiino, 1954;Edwards and Bargeron, 1968) is indicated in some patients with congenital heart disease associated with diminished pulmonary blood flow. The procedure represents a major interference with pulmonary haemodynamics. The blood supply to the right lung then comes from the superior vena cava and from the bronchial collaterals. The blood to the left lung comes from the inferior vena cava and from the systemic vascular bed via an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Patients who have undergone the Fontan procedure with or without a previous Glenn shunt for tricuspid atresia have a low pulsatile pulmonary blood flow. Perfusion studies in patients with Glenn shunts alone have shown this is associated with a maldistribution of pulmonary blood flow manifested by an increased distribution to the lower lung lobes (2)(3)(4)(5). In addition long term follow-up after Glenn shunts has revealed the development of pulmonary arteriovenous fistulae in the lower lobes (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who have undergone the Fontan procedure with or without a previous Glenn shunt for tricuspid atresia have a low pulsatile pulmonary blood flow. Perfusion studies in patients with Glenn shunts alone have shown this is associated with a maldistribution of pulmonary blood flow manifested by an increased distribution to the lower lung lobes (2)(3)(4)(5). In addition long term follow-up after Glenn shunts has revealed the development of pulmonary arteriovenous fistulae in the lower lobes (6).…”
Section: Discussionmentioning
confidence: 99%
“…The patients had a mean oxygen saturation of 92 2 5% at with a similar hernodynamic picture (2)(3)(4)(5) as well as long-term rest and saturation after exercise (87 . ' ?, p evidence of the development of pulmonary arteriovenous fistulae 0.005)' There Were in Vn/Vo27 (6) in the lower lung lobes.…”
Section: F 44 Torrmentioning
confidence: 97%
“…The most popular amongst these for a number of years were absence of pulsatile pulmonary blood flow to the right lung, and dependent flow to the right lower lobe, reflected in a decreased ratio of perfusion between the upper and lower lobes. 24 This latter finding was thoroughly documented in 1969 by Samanek et al, 40 using a radioisotope technique, and then by others. Data about the incidence of the development of the malformations following the classical Glenn, bidirectional cavopulmonary anastomosis, Fontan operation or Kawashima-type of total cavopulmonary connection is conflicting.…”
Section: Pulmonary Arteriovenous Fistulas: Issues About Incidence Andmentioning
confidence: 76%
“…Some authors reported beneficial effects of pulsatile flow for the pulmonary circulation and respiratory function (61–65), while other authors could not confirm these results (60,66,67). Furthermore, in patients, abnormal distribution of pulmonary blood flow has been observed after the Glenn or Fontan operations (68–70). Such results suggest that nonpulsatile blood flow may affect the pulmonary microvascular circulation.…”
Section: Pulsatile Versus Nonpulsatile For Pulmonary Circulationmentioning
confidence: 99%